Cross‐country study on food consumption patterns and rice away from home: The case of Bangladesh. Issue 1 (30th July 2019) - Hassan, Nazmul; Md. Irfan, Nafis; Roy, Sanjit; Shaheen, Nazma
Abstract: As with most Asian countries, rice dominates Bangladesh in terms of food production and consumption. However, with sustained increase in income, persistent commendable GDP growth, urbanization, and significant reduction in poverty, people tend to consume more diversified food, ready to eat food, and food away from home. The findings from this study, based on data from Bangladesh Bureau of Statistics, lend support to this consumption propensity and indicate that with time rice is becoming cheaper and animal and plant foods are getting dearer and expensive. This implies that the national agricultural policy of Bangladesh must recast to match the future food demand of people and to meet the increasing challenge of reversing the rising prices of non‐staples including animal foods. Nested studies on "rice and food away from home" and estimation of demand elasticity and formulation of food demand equations to determine dietary choices and to find nutritional implications of movements in relative food prices and other exogenous variables, to this effect, will have important policy implications for Bangladesh agriculture–food and health paradigm. Resumen: Como en la mayoría de los países asiáticos, el arroz domina a Bangladesh en términos de producción y consumo de alimentos. Sin embargo, con un aumento sostenido de los ingresos, un crecimiento encomiable persistente del PIB, la urbanización y una reducción significativa de la pobreza, las personas tienden a consumir alimentos más diversificados, alimentos listos para comer y alimentos lejos de casa. Los hallazgos del presente estudio, basados en datos de la Oficina de Estadísticas de Bangladesh, respaldan esta propensión al consumo e indican que con el tiempo el arroz se está volviendo más barato y que los alimentos de origen animal y vegetal se están volviendo cada vez más caros. Esto implica que la política agrícola nacional de Bangladesh debe reformularse para ajustarse a la demanda futura de alimentos de las personas y para enfrentar el desafío cada vez mayor de revertir el alza de los precios de productos no básicos, incluidos los alimentos de origen animal. Los estudios anidados sobre "arroz y alimentos fuera de casa" y la estimación de la elasticidad de la demanda y la formulación de las ecuaciones de la demanda de alimentos para determinar las opciones dietéticas y encontrar implicaciones nutricionales de los movimientos en los precios relativos de los alimentos y otras variables exógenas, para este efecto, tendrán una política importante implicaciones para el paradigma agricultura‐alimentación y salud de Bangladesh. 摘要: 和大多数亚洲国家一样，孟加拉的粮食生产消费中大米占据主导地位。然而，随着收入的稳步增长、值得称赞的持续GDP增长、城市化、以及贫困的显著减少，人们倾向于消费更多样化的食物、即食食品，和外出就餐。现有研究基于孟加拉统计局提供的数据，对上述消费倾向予以肯定，并表示随着时间推移，大米将变得越来越便宜，而动植物食品变得越为稀少和昂贵。这暗示孟加拉国家农业政策必须重新调整以满足未来人们的食品需求，并应对阻止副产品（包括动物食品）价格上涨这一越来越严峻的挑战。就"大米和外出就餐"、需求弹性和食品需求等式的预测（用于确定膳食选择，找出相对食品价格浮动和其他外源性变量的营养意义）而进行嵌套式研究（Nested studies），将对孟加拉农业食品和健康范式产生重要的政策意义。